The Influence of Religiosity on Boycott Participation and Its Influence on Brand Attitude with Brand Loyalty as the Moderating Variable: A Study of Starbucks Consumer in Semarang - Bimo Athala Atsal; Ardiaz Ajie Aryandika (Faculty of Economics and Business Diponegoro University, 2026)
Boycott participation represents a form of ethical consumption as an effort by one or more groups to achieve specific objectives by not buying certain products in the marketplace. This study aims to describe and analyze the influence of religiosity on boycott participation and its impact on brand attitude, with brand loyalty examined as a moderating variable. The population in this study consists of Starbucks consumers in Semarang who have previously purchased Starbucks products and are aware of the boycott issue that impact Starbucks. The sample size used in this study is 100 respondents, obtained using non probability sampling with Lemeshow sampling formula for unknown population. The analytical tool used is SPSS to test simple linear regression and moderated regression analysis (MRA), preceded by validity, reliability, and classical assumption tests. The results show that religiosity has a positive and significant effect on boycott participation and boycott participation has a negative and significant effect on brand attitude. Furthermore, brand loyalty is also found to significantly weaken the relationship between religiosity and boycott participation.